Awakening the sleeping giant in Greece and Portugal? Elites’ and voters’ attitudes towards EU integration in difficult economic times - Freire, A.; Teperoglou, E.; Moury, C. (South European Society and Politics, 2014)
This article explores the extent to which the economic crisis and political responses of the European Union (EU) to austerity policies have contributed to Euroscepticism in Greece and Portugal. We analyse attitudes towards the EU both at the voter and elite level using fresh and innovative data, and by comparing them with data from surveys conducted before the crisis we show assessments of austerity and the bailouts are feeding elite and voter Euroscepticism. In both countries there are signs of a crisis of representation with greater voter-elite incongruence in the representation of EU issues than before the bailout.